Implementation of the My Abilities First Tool: A qualitative study on the perceptions of professionals, caregivers, children, and adolescents with disabilities. - Roselene F Alencar; Egmar Longo; Verónica Schiariti; Caline C A F Jesus; Rocío P Carrión; Carolina D L Alvarez; Monique L G Coelho; Tatiana F C Pereira; Maria C L Cruz; Sanzia S V Melgão; Ana Raquel R Lindquist (PLoS ONE, 2024)
Objective To analyze the perceptions of professionals, caregivers, children, and adolescents with disabilities regarding the implementation of the My Abilities First (MAF) tool in Specialized Child Rehabilitation Centers (CERs). Method This is a qualitative research based on Reflexive Thematic Analysis (RTA). The study involved twenty-seven intentionally selected individuals, comprising 12 physiotherapists, 4 occupational therapists, 11 caregivers, 9 children and 2 adolescents. Participants completed sociodemographic and clinical questionnaires and took part in semi-structured online interviews, focusing on two themes: Positive health approaches and the MAF tool. The study was approved by the local ethics committee (opinion 4.779.175). Results Reflexive Thematic Analysis of the interviews resulted in two themes: (1) Perceptions regarding the MAF tool as an educational and contributory process to enhance the inclusion and participation of children and adolescents with disabilities, and (2) Barriers and facilitators for the implementation process of the MAF tool. The implementation of MAF was identified as a driving factor in promoting equity and increased participation of children and adolescents with disabilities in various settings, including health, education, and leisure. Interviewees highlighted the need to confront attitudinal, communication, and social barriers that may hinder the implementation of the tool. Conclusion The implementation of the MAF tool was perceived as an innovation due to its focus on the abilities of individuals with disabilities. However, there is a need to restructure it to broaden its scope and access to different contexts in order to confront barriers and enhance the inclusion and participation of children and adolescents with disabilities.